2020
DOI: 10.18502/avr.v29i3.3846
|View full text |Cite
|
Sign up to set email alerts
|

The relathinship between tinnitus functional index and tinnitus handicap inventory scores in patients with chronic tinnitus

Abstract: Background and Aim: Tinnitus can affect daily life. The evaluation of the affected aspects of life quality is highly dependent on the sub­jects’perception. Self-report questionnaires have been used to identify these affected aspects. In the present study, the relationship between the Persian versions of tinnitus functional index (TFI-P) and tinnitus handicap inventory (THI-P) was investigated. Methods: This is a comparative cross-sectional study conducted on 28 hearing-impaired and 27 normal hearing subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The TFI is more detailed than the THI because it has a wider range of responses (0-10) than the three responses ("yes", "sometimes" and "no") in the THI. However, our results are consistent with previous research that has concluded that both questionnaires are valid and sensitive to changes for initial assessments of tinnitus severity (Dehghan et al, 2020;Fernandez et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The TFI is more detailed than the THI because it has a wider range of responses (0-10) than the three responses ("yes", "sometimes" and "no") in the THI. However, our results are consistent with previous research that has concluded that both questionnaires are valid and sensitive to changes for initial assessments of tinnitus severity (Dehghan et al, 2020;Fernandez et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with other studies, a good correlation was obtained between the THI and TFI questionnaires at baseline and after the treatment [ 22 , 24 ]. At baseline, the THI provided a higher score than the TFI for a higher tinnitus grade but a lower score for lower tinnitus severity.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, while the THI is the most widely used questionnaire [ 23 ], the TFI has been claimed to evaluate better treatment-related changes [ 19 ]. However, recent studies comparing the global score convergence of both questionnaires showed high convergent validity and strong correlation between them [ 22 , 24 ]. Therefore, the main aim of this study was to compare the ability of the global THI and TFI scores in both intake assessment and responsiveness in a cohort of patients treated with EAE therapy for four months.…”
Section: Introductionmentioning
confidence: 99%
“…Hence some questionnaires have been developed to solve this issue. 9 Questionnaires can be used to assess patients' perception of tinnitus severity and its impacts on their life. Tinnitus Functional Index (TFI) and Tinnitus Handicap Inventory (THI) are the most widely used tinnitus questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…THI is a valid tool for evaluating tinnitus and monitoring treatment effect. 9 The adapted Indonesian version of THI instrument is valid and reliable according to transcultural validation principles by WHO as psychometric instrument on the quality of life in patients with tinnitus, therefore could be utilized as self-assessment of quality of life in patients with tinnitus. 10 The shortcoming of THI is it could not distinguish between sleep disturbances, difficulty concentrating, decreased social enjoyment, and hearing loss.…”
Section: Introductionmentioning
confidence: 99%